Private Tour Guide to Pediatric Coronavirus Disease of 2019 and Multisystem Inflammatory Syndrome in Children in 10 Minutes: What Thoracic Radiologists Need to Know. Issue 1 (January 2021) - Foust, Alexandra M.; Winant, Abbey J.; Restrepo, Ricardo; Liszewski, Mark C.; Plut, Domen; Lee, Edward Y.
Abstract : Filtering through the plethora of radiologic studies generated in response to the coronavirus disease of 2019 (COVID-19) pandemic can be time consuming and impractical for practicing thoracic radiologists with busy clinical schedules. To further complicate matters, several of the imaging findings in the pediatric patients differ from the adult population. This article is designed to highlight clinically useful information regarding the imaging manifestations of pediatric COVID-19 pneumonia, including findings more unique to pediatric patients, and multisystem inflammatory syndrome in children.